Current issues of sustainability in esports - Nyström Anna-Greta; McCauley Brian; Macey Joseph; Scholz Tobias M.; Besombes Nicolas; Cestino Joaquin; Hiltscher Julia; Orme Stephanie; Rumble Ryan; Törhönen Maria (United Kingdom, 2025)
Aims: The aim of the paper is to explore emerging themes, which support the development of a sustainable esports industry.
Methods and results: This study is based on a workshop methodology, which aims to identify and explore topics perceived as most pertinent by individuals with an intimate understanding of the dynamics of the esports context. Two workshops were held with a total of 64 participants, representing both academia and industry stakeholders. Interpretations of the sustainability of esports were thus recorded, developed, critiqued, and refined through social interaction with experts. The results indicate three critical themes to address regarding the development of sustainability of esports, namely a) health and inclusiveness, b) the incomplete industry structure, and c) the immature business logic.
Conclusions: Sustainability refers to the ability of esports to survive or persist. We argue that sustainability is dependent on how well industry stakeholders can address the identified themes. Currently, social sustainability is the primary concern of both practitioners and researchers of esports. Economic sustainability mostly deals with securing business growth, while environmental sustainability is not yet perceived as a relevant topic (e.g., using sustainable technologies and energy-saving related to gaming and competitive events). Structures and processes within esports presently constitute the focus of sustainability in esports.
Keywords: esports, sustainability, economic sustainability, social sustainability